Photo‐Organocatalytic Enantioselective Radical Cascade Enabled by Single‐Electron Transfer Activation of Allenes. Issue 2 (18th November 2019) - Perego, Luca Alessandro; Bonilla, Pablo; Melchiorre, Paolo
Abstract: Allenes are commonly used in metal‐mediated transformations, cycloaddition reactions, and radical processes. However, their activation by single‐electron transfer (SET) is largely underexplored. Herein, we report a visible light‐driven enantioselective organocatalytic process that uses the excited‐state reactivity of chiral iminium ions to activate allenes by SET oxidation. The ensuing allene cation radicals participate in stereocontrolled cascade reactions to deliver chiral bicyclic scaffolds with good enantioselectivity and exquisite diastereoselectivity. Density Functional Theory (DFT) calculations support a mechanism that combines the peculiar chemistry of allene radical cations with polar reactivity. Abstract :